Effect of race on the relationship between child maltreatment and obesity in Whites and Blacks. (2nd January 2020) - Chieh, Angela Y.; Liu, Yang; Gower, Barbara A.; Shelton, Richard C.; Li, Li
Abstract: This cross-sectional study was designed to determine what role race plays in the relationship between obesity and child maltreatment (CM), which is currently unknown. One hundred fifteen participants successfully completed the study, including Whites ( n = 60) and Blacks ( n = 55) of both sexes. CM was assessed using the Childhood Trauma Questionnaire. Total fat, trunk/total fat ratio, visceral adipose tissue (VAT), and VAT/trunk ratio, were measured through Dual Energy X-ray Absorptiometry (DXA) and Corescan software estimation. A significant interaction between identifying as White and having a history of CM was found to predict body mass index (BMI) ( β = 5.02, p = .025), total fat (kg) ( β = 9.81, p = .036), and VAT (kg) ( β = 0.542, p = .025), whereas race by itself was an insignificant predictor. An interaction between having history of physical abuse and identifying as White was found to predict BMI ( β = 6.993, p = .003), total fat ( β = 12.683, p = .010), and VAT ( β = 0.591, p = .018). An interaction between having multiple CM subtypes and identifying as White predicts increased total fat ( β = 5.667, p = .034) and VAT ( β = 0.335, p = .014). Our findings indicate that the relationship between CM and obesity, measured through BMI, total body fat, and VAT, is seen in Whites but not in Blacks. Future research should investigate the nature of this racial influence to guide obesity prevention and target at-risk populations.